Non-coding RNAs involved in the molecular pathology of Alzheimer’s disease: a systematic review - Canoy, Reynand Jay; Sy, Jenica Clarisse; Deguit, Christian Deo; Castro, Caitlin Bridgette; Dimaapi, Lyoneil James; Panlaqui, Beatrice Gabrielle; Perian, Wenzel; Yu, Justine; Velasco, John Mark; Sevilleja, Jesus Emmanuel; Gibson, Anna (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is the leading cause of dementia globally, having a pathophysiology that is complex and multifactorial. Recent findings highlight the significant role of non-coding RNAs (ncRNAs), specifically microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and piwi-interacting RNAs (piRNAs) in the molecular mechanisms underlying AD. These ncRNAs are involved in critical biological processes such as cell proliferation, apoptosis, oxidative stress, amyloid-beta aggregation, tau phosphorylation, neuroinflammation, and autophagy, which are pivotal in AD development and progression. This systematic review aims to consolidate current scientific knowledge on the role of ncRNAs in AD, making it the first to encompass the four types of ncRNAs associated with the disease. Our comprehensive search and analysis reveal that ncRNAs not only play crucial roles in the pathogenesis of AD but also hold potential as biomarkers for its early detection and as novel therapeutic targets. Specifically, the findings underscore the significance of miRNAs in regulating genes involved in key AD pathways such as activin receptor signaling pathway, actomyosin contractile ring organization, and advanced glycation endproducts-receptor advanced glycation endproducts (AGE-RAGE) signaling pathway. This review also highlights the potential of ncRNAs in unveiling novel diagnostic and therapeutic strategies, emphasizing the need for further research to validate their clinical utility. Our systematic exploration provides a foundation for future bioinformatic analyses and the development of ncRNA-based precision medicine approaches for AD, offering new insights into the disease’s molecular pathology and paving the way for innovative treatment strategies. Systematic review registration PROSPERO, https://www.crd.york.ac.uk/prospero/, CRD42022355307.